Risk and Reward Preferences under Time Pressure - Nursimulu, Anjali D.; Bossaerts, Peter (Review of Finance, 2014)
Financial decision making under time pressure, though ubiquitous, is poorly understood; classical and behavioral finance are silent about the time required for a decision to be made. In an experiment, calibrating allowable decision times to 1, 3, and 5 s, we find that classical moment-based preferences reflect time-invariant sensitivity to expected reward, purchase impulsiveness under extreme time pressure, and decreased aversion to variance and increased aversion to skewness with decision time. These time-varying sensitivities translate into increased probability distortions and decreased risk aversion for gains under prospect theory (PT). Strikingly, moment-based theory provides a better fit than PT.